Processing and fluid flow characteristics of hot isostatically pressed porous alumina for aerostatic bearing applications - Kwan, Y. B. P (Cranfield University, 1996)
Despite their well known superior load and stiffness characteristics, the wide-spread use of porous aerostatic bearings in preference to other bearing types has been hampered by difficulties in controlling the permeability of the porous material during manufacture and machining, in addition to instability problems caused by the additional volume of air trapped amongst the pores. Recent development in porous aerostatic bearings centres around the use of a thin dense surface layer to overcome the stability problem. The production of single and two-layered porous ceramic structures for aerostatic bearing applications have been investigated using the free-capsule hot isostatic pressing process, and in conjunction with slip and tape castings. The influence of various process parameters on open porosity, and the empirical relationships between porosity, particle size and the resulting fluid flow and structural properties were determined from experimental data. The measurement accuracy and uniformity of temperature within the furnace are identified as the most important factors affecting consistency and predictability of the permeability of the porous substrate. Prototype bearings were produced and tested, based on the above materials. The single-layer bearing was, not unexpectedly, found to be unstable over a wide operating range. The use of a two-layeredb earingm ateriale liminatedth e stabilityp roblem. Initial measurements of the slip coefficient of the porous material in air and at small gaps indicated significant deviation from the Beavers' theory. The effect of velocity slip was found to be significant in both test bearings, and was allowed for by the addition of an equivalent clearance to the bearing gap. The value of the equivalent clearance was deduced from experimental data. The static load characteristics and the pressure profile of both test bearings agreed well with published theories, once the above-mentioned correction for slip was applied.